2005
DOI: 10.1108/09513570510600756
|View full text |Cite
|
Sign up to set email alerts
|

The art of compromise? The individual and organisational legitimacy of “irregular auditing”

Abstract: PurposeIrregular auditing practices, such as false sign‐off, are evidence that proper implementation of work programmes by audit fieldworkers is not always achieved. That such behaviours have been widely attested in the literature raises important questions about the impact they have on the audit engagement. In order to get further insight into the phenomenon, seeks to adopt a qualitative approach, deemed appropriate to complement the mostly quantitative studies available in the literature.Design/methodology/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Furthermore, ethical sensitivity was not examined in this study, and respondents may not have identified these behaviours as involving an ethical dilemma. Conflicting arguments have been presented in the literature on the ethicality of URT (AndersonGough et al, 2001;Sweeney and Pierce, 2006) and QTB (Herrbach, 2005;Pierce and Sweeney, 2006). Finally, the measures of perceived ethical culture include statements with truncated response possibilities.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, ethical sensitivity was not examined in this study, and respondents may not have identified these behaviours as involving an ethical dilemma. Conflicting arguments have been presented in the literature on the ethicality of URT (AndersonGough et al, 2001;Sweeney and Pierce, 2006) and QTB (Herrbach, 2005;Pierce and Sweeney, 2006). Finally, the measures of perceived ethical culture include statements with truncated response possibilities.…”
Section: Discussionmentioning
confidence: 93%
“…This study is the first to show that a firms' choice to stretch the boundaries of its practices is contingent on its structural position within its social network. Our focus on this contingency role of social networks distinguishes our approach from previous work that has tended to focus on the diffusion of new practices (Adithipyangkul et al ., 2011;Davis, 1991;Fligstein, 1985;Haunschild, 1993;Herrbach, 2005;Snyder et al ., 2009). While existing research has uncovered the mechanisms though which interlocks facilitate the adoption of new practices, it has not yet addressed the effect of firms' structural positions on boundary stretching.…”
Section: Discussionmentioning
confidence: 99%
“…Social network theorists claim that social networks can be used as a mechanism for cooptation (Mizruchi, 1996). Our focus on the effect of a firm's structural position within corporate interlocks on boundary stretching practices distinguishes our approach from previous studies on interlocks that focus on the diffusion process of new practices within social networks (Adithipyangkul et al ., 2011;Davis, 1991;Fligstein, 1985;Haunschild, 1993;Herrbach, 2005;Khanna and Thomas, 2009;Snyder, Priem, and Levitas, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Cheng et al (2009)), supervision (e.g. Herrbach (2005)), work-life-balance (e.g. Ladva and Andrew (2014)).…”
Section: Key Factors Affecting Talent Managementmentioning
confidence: 99%